The Relationship Between Skipping Meals, Sedentary Behavior, and Sleep Duration with the Incidence of Overweight in Final-Year University Students - Rachel Florensia Kurnia Putri; Fanny Novanty Nur Hanifah; Kezia Elian Devina; Dewi Kusumawati (Poltekkes Kemenkes Semarang, 2026)
Background: Overnutrition is a nutritional problem characterized by excess body weight resulting from excessive fat accumulation in adipose tissue. Meal skipping, sedentary behavior, and inadequate sleep duration are factors that may contribute to overnutrition, particularly among university students who often have irregular lifestyles. Objective: To determine the association between meal skipping, sedentary behavior, and sleep duration with overnutrition among final-year students at Kusuma Husada University, Surakarta. Methods: This observational study employed a cross-sectional design involving 84 students selected through random sampling. Overnutrition status was determined through body weight and height measurements and assessed using Body Mass Index (BMI). Meal-skipping behavior was assessed using the Meal Skipping Questionnaire, sedentary behavior using the Sedentary Behaviour Questionnaire (SBQ), and sleep duration using the Sleep Timing Questionnaire (STQ). Data were analyzed using the Spearman Rank correlation test with a significance level of p < 0.05. Results: A total of 25.3% of respondents were classified as having overnutrition. A significant association was found between meal skipping and overnutrition (p = 0.043; r = 0.223). No significant associations were found between sedentary behavior and overnutrition or between sleep duration and overnutrition (p > 0.05). Conclusion: There was a weak association between meal skipping and overnutrition, whereas sedentary behavior and sleep duration were not associated with overnutrition among final-year university students.